The Influence of Welfare and Burnout on Honorary Islamic Teachers Performance at Primary Level in Pamboang District, Majene Regency - Syamsul, Muhammad Ayyub (International Journal of Islamic Studies, 2023)
Honorary teachers play a role In order to implement education successfully in Indonesia. However, the reality is that some honorary teachers still don't perform at their best. The welfare and susceptibility to burnout of honorary teachers are the determining elements in their performance. Based on these findings, the purpose of this study is to assess the level of welfare, burnout, and performance of honorary teachers and to ascertain the impact of welfare and burnout on performance, particularly for honorary Islamic Teachers at the elementary school level in Pamboang District, Majene Regency. The researcher use ex post facto research with Quantitatif method. The 30 honorary Islamic Teachers who teach at the elementary level in Pamboang District were all selected as research samples. Additionally, three assessment tools—the teacher wellbeing questionnaire, the assessment Burnout Inventory (MBI) to assess burnout, and the teacher performance questionnaire—are used in this study. Using the SPSS Ver. 25 software and Microsoft Excel Ver. 2019 software, data were analyzed using descriptive and inferential analysis approaches. The research finding descriptively show that the teachers mean score for welfare lever reach 32,5 which is in the low category's class interval. The average burnout level is 31.4, which falls within the medium category class interval. The class interval classifies the mean score at the performance level, 52.1, as quite good. 1) There is a positive and substantial influence of welfare on the performance of honorary Islamic teachers, according to the findings of simple and multiple regression analysis, with a computed t value > t table (4.717 > 2.048) and a significance of 0.000 0.05, therefore maka is accepted.